A Socially Critical View Of The Self-Managing School - Smyth, John (Taylor & Francis, 1993)
The shift from the model of central government educational control to school- based management has been widely adopted and acclaimed and has created the general impression of increased democracy and participation.; The international contributors to this book tackle this important policy issue and look behind the scenes of the moves towards school self- management. They investigate the phenomenon of the self-managing school, Why It Is Happening Now, What Is The Truth Behind This Notion And The problems which lie behind devolution and self-management.; The self- managing school, it is claimed is not about "grassroots democracy" or "parent participation" but absolutely the reverse and this contradiction is best understood in terms of the ideology of the New Right. Enlightened and informed perspectives of the reality behind school self-management suggest that the devolution of power is only superficial. Hierarchies continue to exist as unequally funded schools which perpetuate class, gender and ethnic divisions. The mechanism involved promotes the Survivial Of The Fittest Through Notions Of Choice.; For Those Involved in school management and education generally, this book should provide a useful insight into the struggle surrounding the control of schooling.